Identification of the first nonsense CDSN mutation with expression of a truncated protein causing peeling skin syndrome type B. (December 2013) - Mallet, A.; Kypriotou, M.; George, K.; Leclerc, E.; Rivero, D.; Mazereeuw‐Hautier, J.; Serre, G.; Huber, M.; Jonca, N.; Hohl, D.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Peeling skin disease (PSD) is a generalized inflammatory genodermatosis. PSD is caused by autosomal recessive nonsense mutations in the human corneodesmosin gene (CDSN), which lead to total corneodesmosin deficiency. What does this study add? This study reveals a new nonsense mutation in the human CDSN gene, which leads to a truncated form of corneodesmosin and is responsible for PSD.